NEWLY DISCOVERED MASSIVE GLACIAL BOULDER IN NORTHWESTERN POLAND: IMPLICATIONS AND PROSPECTS FOR SUSTAINABLE REGIONAL GROWTH - Maria GÓRSKA-ZABIELSKA (Geo Journal of Tourism and Geosites)
The aim is to recognise the importance and role of geodiscovery as part of a wider sustainable local development strategy to benefit residents and tourists alike. The research was conducted on a massive erratic boulder discovered in February 2024, in NW Poland. The study included the collection of data on dimensions, petrographic type, erratic boulder type and specific microforms indicating the influence of morphogenetic processes from subglacial, periglacial and modern environments on the erratic boulder. The Jarosik Boulder in northwest Poland is crucial for advancing earth sciences, ecological awareness, and regional economic development. Residents of Grabowo and Kamień Pomorski value and monitor the area's geo-diversity to anticipate environmental changes. The boulder has a strong emotional connection with locals, who actively engage in its preservation and online discussions. Promoting the boulder can enhance the region's environment, culture, and well-being, contributing to sustainable development. Local initiatives and effective promotion through media and community events are essential for boosting geotourism and benefiting both residents and visitors. Recognised as a cultural asset, Jarosik Boulder can realise its full potential through the commitment of local authorities to improving the community. As a unique aspect of geodiversity in NW Poland, Jarosik Boulder serves as a catalyst to promote geological science, support environmental education efforts, and foster sustainable economic and regional development.